X-RAY IMAGING DIAGNOSTIC APPARATUS - OISHI SATORU; ABE SHINGO (2016)
PROBLEM TO BE SOLVED: To provide an X-ray imaging diagnostic apparatus which can easily determine a working angle indicating an appropriate arm position in consideration of a skin incident dose.SOLUTION: An X-ray imaging diagnostic apparatus includes: a skin incident dose calculation part which calculates a skin incident dose into a subject; a skin incident dose information generating part which generates dose data indicating information on the skin incident dose to the subject, from the calculated skin incident dose; and a composite image display part which displays a composite image superimposing the dose data indicating the information on the skin incident dose on a three-dimensional image obtained by capturing the subject.SELECTED DRAWING: Figure 3 【課題】皮膚入射線量を考慮した適切なアームの位置を示すワーキングアングルを容易に決定することができるＸ線画像診断装置を提供する。【解決手段】本実施形態に係るＸ線画像診断装置は、被検体への皮膚入射線量を計算する皮膚線量計算部と、計算された前記皮膚入射線量から、前記被検体への皮膚入射線量情報を示す線量データを生成する皮膚入射線量情報生成部と、前記被検体を撮影して得られた３次元画像に前記皮膚入射線量情報を示す線量データを重畳させた合成画像を表示する合成画像表示部と、を備える。【選択図】 図３